Seroprevalence of Avian Influenza A(H5N6) Virus Infection, Guangdong Province, China, 2022 - Yang Wang; Chunguang Yang; Yong Liu; Jiawei Zhang; Wei Qu; Jingyi Liang; Chuanmeizi Tu; Qianyi Mai; Kailin Mai; Pei Feng; Wenjing Huang; Zhengshi Lin; et al. (Emerging Infectious Diseases, 2024)
In 2022, we assessed avian influenza A virus subtype H5N6 seroprevalence among the general population in Guangdong Province, China, amid rising numbers of human infections. Among the tested samples, we found 1 to be seropositive, suggesting that the virus poses a low but present risk to the general population.